Spain transformed the Franco dictatorship, 1959-1975 - Townson, Nigel (Palgrave Macmillan, 2007)
Spain Transformed addresses the sweeping social and cultural changes that characterized the late Franco regime. This wide-ranging collection reassesses the dictatorship's latter years by drawing on a wealth of new material and ideas, using an interdisciplinary approach.